2004
DOI: 10.1093/intimm/dxh176
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal enterotoxins condition cells of the innate immune system for Toll-like receptor 4 stimulation

Abstract: In this report we examined overlap between superantigen (SAg) and Toll-like receptor 4 (TLR4) stimulation of the innate immune system. Before in vivo stimulation we found that mouse splenic DCs expressed unexpectedly low levels of surface TLR4 compared to macrophages. In response to LPS, TLR4 gene expression in fractionated spleen cells was downregulated. By comparison, surface TLR4 staining with the Sa15-21 mAb showed little downregulation, and the anti-TLR4 MTS510 mAb showed decreased staining, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…As BLP is the most abundant cell wall component in both Gram-positive and Gram-negative bacteria, this novel finding may explain the mechanisms behind massive proinflammatory cytokine release in sepsis caused by superantigensecreting bacteria (28). Superantigens have been shown to upregulate the expression of both TLR2 and TLR4 on isolated human monocytes (6,7,26), which was also observed in the current study (data not shown). Although this upregulation by superantigen of TLRs may play a role in the increased responsiveness of the innate immune system in superantigen-mediated septic shock, other research has shown that in patients with severe sepsis, TLR expression does not correlate well with ligand sensitivity (31,32).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As BLP is the most abundant cell wall component in both Gram-positive and Gram-negative bacteria, this novel finding may explain the mechanisms behind massive proinflammatory cytokine release in sepsis caused by superantigensecreting bacteria (28). Superantigens have been shown to upregulate the expression of both TLR2 and TLR4 on isolated human monocytes (6,7,26), which was also observed in the current study (data not shown). Although this upregulation by superantigen of TLRs may play a role in the increased responsiveness of the innate immune system in superantigen-mediated septic shock, other research has shown that in patients with severe sepsis, TLR expression does not correlate well with ligand sensitivity (31,32).…”
Section: Discussionsupporting
confidence: 85%
“…This makes them capable of activating up to 20% of the T cell repertoire in an uncontrolled manner (4). Recently, however, superantigens have been shown to activate the innate immune system independently of T cells (6,7,26,27) through direct binding of superantigens to MHC class II receptors on monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 This data complements that from adoptive transfer models in which CD28 is required for LPS to enhance CD4 T cell clonal expansion. 90 The greater dependency of peptide-stimulated CD4 T cells on CD28 signaling may result from an ability of superantigens to activate APCs better than peptides, 91,92 or to deliver stronger TCR signals to both CD4 and CD8 T cells.…”
Section: B Lps Promotes T Cell Survival Through Accessory Cellsmentioning
confidence: 99%
“…2a depicts the forward (size) and side (granularity) scatter dot plot of PBS treated PECs harvested at 24 h. Because we were interested in activated cells such as macrophages which have high side scatter as we have observed before [24], the R2 and R3 gates were selected as shown in Fig. 2a.…”
Section: Comparison Of the Broad Cellular Innate Immune Response Elicmentioning
confidence: 99%